2004
DOI: 10.1097/01.asn.0000125619.27422.8e
|View full text |Cite
|
Sign up to set email alerts
|

BMP-7 Modulates Hyaluronan-Mediated Proximal Tubular Cell-Monocyte Interaction

Abstract: Abstract. Increased synthesis of hyaluronan (HA) in the renal corticointerstitium has been documented in renal injury, although the functional significance of this is unclear. The aim of the work presented in the current study was to examine the role of HA in monocyte binding by proximal tubular cells (PTC). Using the PTC line HK-2, the authors show that unstimulated cells formed pericellular HA cable-like structures that bound mononuclear leukocytes via their cell surface CD44. Stimulation with bone morphogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 48 publications
(41 reference statements)
4
53
0
Order By: Relevance
“…Many cell types assemble HA in an organized pericellular coat in vitro, in which the HA is anchored to the cell surface by CD44 (16,(31)(32)(33)(34)(35). Our recent studies in proximal tubular epithelial cells have investigated the roles of the I␣I family of hyaladherin proteins, together with TSG-6 and the HA-binding proteoglycans bikunin and versican, in the macromolecular assembly of HA by PTC (16,25,35,36). The results demonstrated that the TSG-6-mediated formation of I␣I HC⅐HA complexes was critical for the formation of a pericellular HA matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Many cell types assemble HA in an organized pericellular coat in vitro, in which the HA is anchored to the cell surface by CD44 (16,(31)(32)(33)(34)(35). Our recent studies in proximal tubular epithelial cells have investigated the roles of the I␣I family of hyaladherin proteins, together with TSG-6 and the HA-binding proteoglycans bikunin and versican, in the macromolecular assembly of HA by PTC (16,25,35,36). The results demonstrated that the TSG-6-mediated formation of I␣I HC⅐HA complexes was critical for the formation of a pericellular HA matrix.…”
Section: Discussionmentioning
confidence: 99%
“…BMP7 signaling limits excessive tissue injury by suppressing initiation of the inflammatory response by tubular epithelial cells. 4,[11][12][13] Immune surveillance is required for maintenance of the healthy kidney, and antagonism of BMP7 may therefore be necessary for tissue homeostasis. Upon ischemic injury, release of antagonism by degeneration of the CHRDL1-expressing S3 segment would facilitate BMP7 signaling required to counteract the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, BMP7 changes the conformation of cell-surface hyaluronic acid on proximal tubule cells, altering monocyte binding and preventing increased TGF-␤ production. 12,13 BMPs signal by binding serine-threonine kinase receptors, which phosphorylate Smad transcription factors. Association of Smads with cell type-specific transcription factors determines transcriptional outcomes, enabling context-dependent responses.…”
mentioning
confidence: 99%
“…We also recently identified a novel mechanism by which monocytes interact with PTC and is dependent on CD44-mediated adhesion of monocytes to hyaluronan (HA)-based structures generated on the PTC cell surface (9). We also demonstrated that bone morphogenic protein-7 (BMP-7) stimulates the formation of HA cables and also increases HA-dependent monocyte interaction with PTC.…”
mentioning
confidence: 93%